Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people--violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."-- Résumé de l'éditeur.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

L'âme en tannage de Natasha Kanapé Fontaine : souveraineté orale, territoriale et mémorielle - Marcoux, Gabrielle (Canadian Review of Comparative Literature / Revue Canadienne de Littérature Comparée, 2017)
Nous proposons que le slam L’âme en tannage démontre une tentative explicite de décolonisation à travers une résistance et une résurgence culturelles, exprimées notamment par le biais d’une mise en emphase de différences identitaires nettes et assumées, contemporaines et historiques, entre la narratrice autochtone et son destinataire non-autochtone. Nous sommes d’avis que l’expression critique de relations de réciprocité et d’interdépendance reliant les notions de la territorialité, de l’oralité et de la mémoire collective sert d’assise au programme de décolonisation mis en branle par la jeune femme. Grâce à l’utilisation de l’ironie, de néologismes critiques, de déterminants antagonistes et de sonorités char- gées au plan culturel, l’auteure établit effectivement des liens de corrélation puissants entre ses projets de souveraineté orale, de souveraineté territoriale, et de souveraineté mémorielle. À travers une analyse sommaire de passages extraits du slam de Kanapé Fontaine, nous tenterons d’analyser ces quelques stratégies discursives et épistémologiques de décolonisation proposées par la jeune poète innue, témoignant vraisemblablement de la résolution de ces scissions identitaires internes évoquées par Lamy au profit d’un programme explicite et organisé de résistance et de résurgence culturelles, sociales et politiques.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; arts; discipline; discours dominant; environnement; femmes* autochtones; militance; mémoire; poésie; périodes historiques; ressource en ligne; slam; système colonial; systèmes d'oppressions; territoire; thématiques; violences; violences coloniales; écriture des femmes*; études littéraires

Femmes autochtones: la violence coloniale et ses avatars - Perreault, Julie (Relations, 2017)
Au Québec et au Canada, les femmes autochtones sont parmi les plus susceptibles d'être la cible de violences; une réalité qui met en lumière une histoire de colonialisme qui continue de faire des victimes.
Keywords: amériques; approches et analyses; canada; cours; discipline; femmes* autochtones; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; québec; racisme; régions géographiques; science politique; science politique et droit; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; violences